ANALISIS KESULITAN MENULIS KALIMAT SEDERHANA PADA SISWA KELAS II SD NEGERI 1 LANDUNGSARI - Bilqis Khawai Hayudza; Dinah Alfiyah Zahra; Nola Feriska Ramadani; Dwi Nur Lestari; Beti Istanti Suwandayani (STKIP Subang, 2025)
This study aims to describe the difficulties experienced by second-grade students in writing simple sentences at Landungsari 1 Public Elementary School and the factors that influence them. Using a descriptive qualitative approach, data were collected through observation, informal interviews with classroom teachers, and documentation of students' writing. The results of the study show that most students still experience difficulties in the mechanical aspects of writing, such as the use of capital letters, periods, consistency in letter form, letter size, and spacing. Difficulties in sentence structure were also found, such as missing subjects or predicates and irregular word order. Factors causing these difficulties included suboptimal fine motor skills, poor visual memory, lack of motivation to learn, and dependence on example sentences. External factors such as minimal parental guidance and a lack of literacy at home also exacerbated students' writing abilities. These findings confirm that difficulties in writing simple sentences are multifactorial and require varied learning interventions, ranging from strengthening fine motor skills, using visual media, process-based learning strategies, to increasing parental involvement in literacy activities. This study provides a basis for teachers to design more effective and contextual writing lessons.